Kualifikasi Da'i: Komparasi Konseptual Retorika Dakwah dan Retorika Aristoteles - Hasanah, Umdatul (Jurnal Komunikasi Islam, 2020)
The presence of Islamic preachers in the current Indonesia has marked the awakening of the world of da’wah. However, this phenomenon also has raised people's criticisms concerning the competence and credibility of Muslim preachers (da'i). This article reports on a library research regarding the conceptual comparison of Islamic propagation (da'wah) and Aristotle's rhetoric with regard to the qualifications of da'i. The results of this study has indicated that the rhetoric of da'wah which primarily rooted from divine revelation has conceptual relevance to Aristotle's rhetoric; ethos, pathos and logos. In this regard, a da'i is not only required to have credibility with moral qualities, good intentions and goals. In addition, they are also required to have the authority and scientific competence as well as an understanding of the nature of mad'u.